The fountain of Latona : Louis XIV, Charles Le Brun, and the gardens of Versailles - Hedin, Thomas F., 1944- (Penn studies in landscape architecture., 2022)
"In a many-sided examination of the artistic, cultural, and political worlds of Louis XIV, Thomas F. Hedin masterfully reveals how and why an elaborate fountain depicting the origin of frogs came to be the centerpiece of the gardens of Versailles"--